2018
DOI: 10.1111/jsr.12774
|View full text |Cite
|
Sign up to set email alerts
|

How to organise teaching activities for the scoring of cardiorespiratory polygraphies? Experiences from three Swedish Sleep Society teaching courses

Abstract: Education in the scoring of sleep‐disordered breathing is organised differently and data on the evaluation of teaching strategies based on student ratings are sparse. The aim of the study was to analyse the gain in theoretical and practical knowledge achieved during different course settings offered by a national sleep society. The course contained 1 hr of theoretical teaching (scoring rules and recording methodology) and 2.5 hr of practical scoring (physiological breathing, obstructive/central sleep apnea and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Another aspect, which is also unexplored, is whether the knowledge tested is relevant for the final clinical decision making, the diagnostic accuracy. However, one study performed in students of three Swedish sleep scoring courses showed that the student's self‐assessment of their increase in knowledge and satisfaction with the scoring course did not differ between the professions or the level of experience at the start of the course (Grote, 2019). From this indirect evidence it can be hypothesised that the current practice in the ESRS examination may be a valid approach to use at least similar cases for sleep medicine experts from various academic backgrounds.…”
Section: Critical Appraisal and Future Perspectivesmentioning
confidence: 99%
“…Another aspect, which is also unexplored, is whether the knowledge tested is relevant for the final clinical decision making, the diagnostic accuracy. However, one study performed in students of three Swedish sleep scoring courses showed that the student's self‐assessment of their increase in knowledge and satisfaction with the scoring course did not differ between the professions or the level of experience at the start of the course (Grote, 2019). From this indirect evidence it can be hypothesised that the current practice in the ESRS examination may be a valid approach to use at least similar cases for sleep medicine experts from various academic backgrounds.…”
Section: Critical Appraisal and Future Perspectivesmentioning
confidence: 99%